Efektivitas Model Blended Learning Dalam Meningkatkan Pembelajaran - Rizki, Umi; Putri , Eka; Amin, Ahmad; Citra, Dania; Andini , Eka Putri; Abu, Wismanto (Cendekia : Jurnal Pendidikan dan Keagamaan, 2025)
In the 21st century, learning has entered the digital era where educational practitioners have developed many digital-based learning such as online learning. However, online learning still requires face-to-face learning. So, education experts combined the two into a new learning theory called Blended Learning. Blended learning includes face-to-face, online, and offline learning, allowing students to access it through application programs. Research shows that blended learning is more effective than separate online or face-to-face learning. Blended learning applications can use a variety of combinations, such as 50/50, 75/25, or 25/75, depending on the allocation of learning time and student characteristics. In designing blended learning, it is important to pay attention to how to make the learning interesting and appropriate to students' learning styles.